Expression profiling of plasmodium berghei HSP70 genes for generation of bright red fluorescent parasites - Hliscs, Marion; Nahar, Carolin; Frischknecht, Friedrich; Matuschewski, Kai (PLOS ONE, 2013)
Live cell imaging of recombinant malarial parasites encoding fluorescent probes provides critical insights into parasite-host interactions and life cycle progression. In this study, we generated a red fluorescent line of the murine malarial parasite Plasmodium berghei. To allow constitutive and abundant expression of the mCherry protein we profiled expression of all members of the P. berghei heat shock protein 70 (HSP70) family. We identified PbHSP70/1, an invariant ortholog of Plasmodium falciparum HSP70-1, as the protein with the highest expression levels during Plasmodium blood, mosquito, and liver infection. Stable allelic insertion of a mCherry expression cassette into the PbHsp70/1 locus created constitutive red fluorescent P. berghei lines, termed Pbred. We show that these parasites can be used for live imaging of infected host cells and organs, including hepatocytes, erythrocytes, and whole Anopheles mosquitoes. Quantification of the fluorescence intensity of several Pbred parasite stages revealed significantly enhanced signal intensities in comparison to GFP expressed under the control of the constitutive EF1alpha promoter. We propose that systematic transcript profiling permits generation of reporter parasites, such as the Pbred lines described herein.